Bureaucratic behavior in democracy: A case study - Werner W. Pommerehne; Bruno S. Frey (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1977)
This paper analyzes bureaucracy within the context of the politico-economic framework using the rational choice approach. Bureaucracy interacts with various groups of decision-makers, and its influence depends on institutional differences, in particular representative democracy with or without referendum. Theoretical and empirical analysis for Swiss cities suggests that (1) there is little evidence for any significant influence on policy outcome by bureaucrats qua voters; (2) there is evidence that bureaucracy has a direct influence on the supply side; (3) it is not useful to view bureaucracy to be in an isolated position of a monopolist.
Keywords: 330